Quinta do Assento, Preservar a memória. - Rui Pedro de Carvalho Vieira (2013)
"is thesis bases itself on the formulation of a possible intervention strategy in a particular case study, named "Quinta do Assento", which purpose is to maintain and reinforce it is unique, notable and identi!able characteristics.From it is analysis, we note interesting and valid features like the strong relationship between architecture and landscape, the presence of water in the property and the existence of several elements that guide you to outdoor recreational spaces. Registration and detailed documentation of these facts have the purpose to answer the questions asked and are an important document which will preserve for future memory the object of study which is in ruins. As a result of this work, outdoor spaces gain new purpose, guidelines are presented for intervention in the set, while preserving the essential and discarding the accessory, and some guidelines for a possible expansion of the existing construction.